Primary Immunodeficiencies With Defects in Innate Immunity: Focus on Orofacial Manifestations - Jung, Sophie; Gies, Vincent; Korganow, Anne-Sophie; Guffroy, Aurélien (Frontiers in Immunology, 2020)
The field of primary immunodeficiencies (PIDs) is rapidly evolving. Indeed, the number of described diseases is constantly increasing thanks to the rapid identification of novel genetic defects by next-generation sequencing. PIDs are now rather referred to as “inborn errors of immunity” due to the association between a wide range of immune dysregulation-related clinical features and the “prototypic” increased infection susceptibility. The phenotypic spectrum of PIDs is therefore very large and includes several orofacial features. However, the latter are often overshadowed by severe systemic manifestations and remain underdiagnosed. Patients with impaired innate immunity are predisposed to a variety of oral manifestations including oral infections (e.g. candidiasis, herpes gingivostomatitis), aphthous ulcers, and severe periodontal diseases. Although less frequently, they can also show orofacial developmental abnormalities. Oral lesions can even represent the main clinical manifestation of some PIDs or be inaugural, being therefore one of the first features indicating the existence of an underlying immune defect. The aim of this review is to describe the orofacial features associated with the different PIDs of innate immunity based on the new 2019 classification from the International Union of Immunological Societies (IUIS) expert committee. This review highlights the important role played by the dentist, in close collaboration with the multidisciplinary medical team, in the management and the diagnostic of these conditions.